Peran Peran Kepuasan Dalam Memediasi Pengaruh “Online Review”, Kualitas Pelayanan, Dan Lokasi Terhadap Loyalitas Konsumen pada Restoran “Warong Legong” di Desa Keramas, Gianyar, Bali - Massenga, Lidjah Magdalena; Budiani, Ni Putu Ariesta; Ni Luh Suastuti; Pranadewi, Putu Mira Astuti; Arcana, I nyoman (JURNAL GASTRONOMI INDONESIA, 2025)
Online consumer reviews on Google Reviews, Zomato and Tripadvisor help restaurants monitor the quality standards of their products and services to consumers. In the face of increasingly tight competition, restaurants must pay attention to customer experience, in terms of product quality, price, strategic location, and service quality, so that customers feel satisfied with their dining experience. This study aims to analyze the role of satisfaction "in mediating the influence of "online review", service quality, and location on consumer loyalty at Warong Legong. By using SEM PLS analysis, this study concluded that: 1) There is an effect of "online review" on satisfaction; 2) There is an influence of "online review" on consumer loyalty; 3) There is an influence of service quality on consumer satisfaction; 4) Service quality factors have a significant and positive effect on consumer loyalty; 5) There is an influence of service quality on consumer satisfaction; 6) There is an influence of service quality on consumer loyalty; 7) There is an effect of satisfaction on consumer loyalty; 8) Satisfaction can mediate the influence of online reviews, service quality and location on consumer loyalty; and 9) Loyalty is influenced by consumer satisfaction as an intervening variable.